Vulnerabilidade hídrica à ocorrência de eventos de secas e inundações no semiárido cearense - Macêdo, Joalana Araújo (2023)
Water vulnerability occurs when the population is prone to suffering the adverse effects of extreme weather events, due to not having the means to protect themselves and due to the inability to meet water demand. This research is based on the hypothesis that the municipality located in the semi-arid region of Ceará suffers from the occurrence of climatic extremes, represented by the binomial, drought and flood, and it is possible to assess water vulnerability to these events, based on environmental factors and using water banks. secondary data. The general objective is to understand water vulnerability in the municipality of Forquilha, located in a semi-arid environment, based on the use of environmental indicators, given the occurrence of droughts and the increase in the volume of precipitation. The work was developed in the municipality of Forquilha, located in the semi-arid region of the State of Ceará. Using a methodological approach based on the assessment of water vulnerability, based on environmental indicators. In Forquilha, the effects of climate fluctuations give rise to drought and flood events that affect the municipality, resulting in water vulnerability.